# How do I solve #4(x-3)-(x-5)=0#?

Refer to the explanation for the process.

Resolve:

Extend.

Make it simple.

By signing up, you agree to our Terms of Service and Privacy Policy

To solve the equation 4(x-3)-(x-5)=0, you would follow these steps:

- Distribute the terms inside the parentheses: 4x - 12 - x + 5 = 0
- Combine like terms: 3x - 7 = 0
- Add 7 to both sides: 3x = 7
- Divide both sides by 3: x = 7/3

So, the solution to the equation is x = 7/3.

By signing up, you agree to our Terms of Service and Privacy Policy

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7